The role of election campaigns in enhancing public political participation.(Wasit Provincial Council Elections 2023 as a model) - atheer noori, Rese. (lark, 2024)
Elections are considered an important means of representing democratic governance, serving as a tool for the public to express their opinions in selecting individuals they see capable of assuming responsibilities and achieving their aspirations.Election campaigns are among the most crucial stages of the electoral process and are the essence of political activity preceding the election date. They allow political party candidates to engage in activities and express their political agendas to persuade and attract the public to vote for their candidates in the electoral booth.Given the importance of election campaigns and their impact on the public, the significance of this study arises from the specificity of the electoral event as a communicative activity for political parties participating in the elections of the Iraqi provincial councils. The research results revealed deficiencies in election campaigns, especially in their role in mobilizing and raising public awareness to encourage participation in elections. Campaigns did not provide the public with sufficient insight into the electoral programs of parties and candidates. It was also evident that most researchers relied on clan affiliation in their selection of candidates.